ANALYSIS OF GRAPHICS PIPELINES - Romanyuk, Oleksandr; Bobko, Oleksii; Zavalniuk, Yevhen; Titova, Nataliia; Romanyuk, Serhii; Stakhov, Oleksii (European Science, 2024)
In the work, the concept of graphics pipeline is analyzed. The features of OpenGL and DirectX graphics pipelines are compared. The perspectives of graphics pipeline development are discussed.